Political Patronage and Bureaucracy: Studies in Nigeria and Indonesia - Elekwachi, Eze; Ufomba, Henry (CV. Era Digital Nusantara, 2024)
Abstract: The realization of effective governance in any nation hinges on the provision of ample services for its citizens. Responsible for the efficient delivery of these services is the executive arm of government, overseen by the civil service. The ideal functioning of the civil service necessitates the appointment of highly intelligent and qualified personnel recruited through a merit-based system. Regrettably, in both the Ebonyi state civil service and Indonesia, the actual experience deviates significantly from this esteemed ideal. Purpose: The primary objective of this investigation is to evaluate the correlation between political patronage and inefficiency in the delivery of public services within Ebonyi State. Additionally, the study seeks to identify and analyze instances of bureaucratic patronage in Indonesia. Design/Methodology/Approach: The research employed a survey research methodology to gather data. The study drew information from both primary sources, collected directly from the surveyed subjects, and secondary sources, which encompassed existing data and literature relevant to the research topic. Findings: The findings of the study unveiled that the inefficiencies observed in the service delivery of the Ebonyi State Civil Service are directly linked to the practice of political patronage. Likewise, the investigation established that selective promotion and recruitment practices within the Ebonyi state civil service are directly influenced by political patrons. Additionally, the study identified that the influence of godfathers within the service framework contributes significantly to maintaining high discipline among civil servants in Ebonyi state. In the context of Indonesia, the research illuminated that patronage by bureaucrats is prevalent. Despite the expectation of bureaucratic neutrality in enforcing regulations, the study acknowledged that the relationship between politicians and bureaucrats is inseparable, leading to political exchanges aimed at securing benefits. Originality/value: This research represents a unique contribution to the existing body of knowledge as it pioneers a comparative analysis of political patronage and bureaucracy in Nigeria and Indonesia. The novelty of this study lies in its exploration of similarities and differences in the manifestation and impact of political patronage within the bureaucratic frameworks of both nations, providing valuable insights into cross-cultural dynamics in public administration.